Effect of β-SiAlON content on the sintering and bacteriostatic properties of β-SiAlON–Si3N4 composite ceramics. Issue 22 (15th November 2022) - Li, Liya; Gao, Jinxing; Chang, Guanglei; Mu, Jinghua; Xu, Enxia; Liu, Xinhong; Yan, Juan; Zhou, Huoxiang; Zhang, Liguo
Abstract: β-SiAlON–Si3 N4 composite ceramics were prepared by varying β-SiAlON content in the raw material and the content effect on the sintering, phase, microstructure and bacteriostatic properties of the resultant ceramics are studied. It was found that the main crystal phase was determined to be β-Si3 N4 . With an increase of the content of β-SiAlON, the crystal phase changed from α to β, the sintering became denser, the bulk density and compressive strength increased, the porosity decreased gradually. When the β-SiAlON content reached 30 wt%, the optimal properties were observed for a ceramic prepared (bulk density of 2.63 g/cm 3, porosity of 17.35%, and compressive strength of 1093 MPa). Ion release, chemical erosion and bacteriostatic testing showed that ammonia nitrogen was released from the ceramics in deionized water, which inhibits the proliferation of bacteria. Finally, the antibacterial mechanism of β-SiAlON–Si3 N4 composite ceramics was proposed. The β-SiAlON–Si3 N4 composite ceramics prepared in this study show potential for future application in the field of biological bacteriostasis as a bone substitute material.